A prisca theologia de Marsilio Ficino - Placido, Daniel Rodrigues (2023)
The Italian philosopher, priest, translator, astrologer and magician Marsilio Ficino (1433-1499) elaborated, in the context of the Renaissance, the notion of prisca theologia (ancient theology), enunciating the existence of an ancient wisdom conveyed by different philosophies and religions, through of a chain of wise men or ancient theologians (Zoroaster, Hermes, Orpheus, Aglaophemus, Pythagoras and Plato), who would also be in full agreement with the truths of Christianity. Ficino practically addressed and re-elaborated the theme of prisca theologia throughout his entire intellectual career, from his youth texts to his last texts, letters, translations and commentaries.This dissertation aims to: a) identify and explain the antecedents of prisca theologia in M. Ficino, in order to understand its motivations and assumptions, based on the authors and references with which it dialogues, in the light of the Renaissance context; b) present the specific contours of this idea in Ficinian works, with special attention to the first texts (1457-1462), including Pimander, Commentary on Philebus, De Christiana religione, Platonic Theology, Letters and other writings, including analyzing variations in the formulation of this notion, to understand its meaning and intention; c) expose and analyze Ficino's debate with some Renaissance authors who developed this notion of prisca theologia, or something close to it; d) as a hypothesis to be verified, to demonstrate that if prisca theologia appears in an embryonic form in ancient and medieval currents and traditions, in agreement within a flexible arch of references, it cannot fully integrate Christianity, a task that, in this way, will be embraced by Ficino, as he was above all a Christian Platonic author of his time, endowed with a vast intellectual and cultural repertoire, capable of dealing simultaneously with pagan traditions and with the Judeo-Christian tradition, in the light of a perception of crisis in philosophy, Christian theology and society in which he lived, seeking reform.